Pyrochlore doped Pr2Sn2O7 ceramics: Electronic transport properties and high NO2 sensitivity. Issue 4 (April 2020) - Zhong, Fulan; Duan, Pei; Han, Cheng; Zheng, Yong; Cai, Guohui; Xiao, Yihong
Abstract: This work proposed pyrochlore doped-Pr2 Sn2 O7 ceramics with electronic transport and NO2 sensitivity through molecular insights into sensing mechanism by DFT. NO2 adsorbed on the p-type semiconductor metal oxide NiO(100) can be decomposed into three stable adsorbed states NO2, NO and O that will obtain electrons from the NiO valence band to form N2 (or N2 O) and O 2−, resulting in an increase of the holes concentration. The results suggest that the response current value of the sensor based on Pr2 Sn2 O7 doped by Ca 2+ at A site is 53.5 times higher than that of commercial YSZ, indicating high sensitivity with 420 nA/ ppm at mild temperature 550 °C. Besides the creation of oxygen-defect sites, the electronic transport is responsible for the improved sensing properties. The electrons on doped Pr2 Sn2 O7 ceramics can complement the hole-accumulation layer and make NO2, NO, O accept electrons quickly to accelerate the rate of the electrochemical cyclic reaction.